Law in everyday life - Seely, John (Oxford University Press, 2003)
A book of practical advice and useful tips on understanding the complex legal jargon encountered in day-to-day life. This lively, accessible, and illustrated guide is divided into two sections. The first includes chapters on all the times you may find it necessary to understand the law, from cradle to grave. Whether having children, buying a car, or making a will you will find help on the subject here. The second half is an easy to use, key quick reference section including an extensive glossary of legal terms, where you can find help on legal issues, and resources for further information